2016
DOI: 10.3390/ijms17071004
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification, Evolutionary Analysis, and Stress Responses of the GRAS Gene Family in Castor Beans

Abstract: Plant-specific GRAS transcription factors play important roles in regulating growth, development, and stress responses. Castor beans (Ricinus communis) are important non-edible oilseed plants, cultivated worldwide for its seed oils and its adaptability to growth conditions. In this study, we identified and characterized a total of 48 GRAS genes based on the castor bean genome. Combined with phylogenetic analysis, the castor bean GRAS members were divided into 13 distinct groups. Functional divergence analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 59 publications
(108 reference statements)
10
68
2
Order By: Relevance
“…In the present study, a total of 77 GRAS genes were identified in cassava. This number is lower than that in Malus domestica (127) [28], Populus (106) [20], and maize (86) [27] but higher than that in Arabidopsis (34) [20], rice (60) [20], Chinese cabbage (48) [19], Prunus mume (46) [21], tobacco (53) [22], castor (48) [23], grapevine (52) [24], Medicago truncatula (68) [25,26], pepper (50) [29], and tea plant (52) [30]. This variation in GRAS gene numbers might be related to gene duplication events or genome size [24].…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In the present study, a total of 77 GRAS genes were identified in cassava. This number is lower than that in Malus domestica (127) [28], Populus (106) [20], and maize (86) [27] but higher than that in Arabidopsis (34) [20], rice (60) [20], Chinese cabbage (48) [19], Prunus mume (46) [21], tobacco (53) [22], castor (48) [23], grapevine (52) [24], Medicago truncatula (68) [25,26], pepper (50) [29], and tea plant (52) [30]. This variation in GRAS gene numbers might be related to gene duplication events or genome size [24].…”
Section: Discussionmentioning
confidence: 86%
“…It is noteworthy that some GRAS proteins considered to be species-specific in previous publications have homologs in cassava. For example, nine cassava MeGRAS genes (MeGRAS22, 23,27,28,29,30,31,34, and 66), together with PtGRAS20 (belong to "Pt20" subfamilly) and RcGRAS27 (29,889.m003282; belong to "Rc_GRAS" subfamily) which was previously regarded as species-specific subfamily [20,23]. They were also clustered with tomato SlGRAS22, which was clustered with pepper-specific "Ca_GRAS" subfamily [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, there is the hypothesis that seed size evolves as part of a spectrum of life history traits, including plant size, plant longevity, juvenile survival rate and time to reproduction (Moles y Westoby 2006). Or that gene complexes seek adaptation to the environment (Xu et al 2016). It is also thought that a reduction in the number of fruits causes an increase in the mass of individual seed (Jofuku et al 2005).…”
Section: Resultsmentioning
confidence: 99%